Cooling and exhumation of the Late Paleozoic Tulasu epithermal gold system, Western Tianshan, NW China: implications for preservation of Pre-Mesozoic epithermal deposits. Issue 2 (2021) - Zhao, Xiao-Bo; Xue, Chun-Ji; Zhao, Wei-Ce; Seltmann, Reimar; Symons, David T.A.
No abstract available